The Present Status of Control and Extent of Infestation with Citrus Leafminer and Scale Insects on Citrus Trees in Tulkarm Area - Yacoub Batta; Thamer Abo-Ahmad; Mohannad Al-Shalabi; Nizar Amran; Nizar Dawood (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This research was conducted to evaluate the present status of citrus orchards in Tulkarm area in terms of extent of infestation with the citrus leafminer and scale insects. Therefore, a questionnaire had been prepared and contained many questions relating to the current infestation and control measures applied by the farmers for both types of insect pests. The answers to questions raised in the questionnaire were directly obtained from farmers in their orchards and then analyzed and interpreted. Results obtained had indicated that 63.6-72.7% of the farmers asked in the questionnaire were profiting from extension services and applying recommended types and doses of insecticides for control of citrus leafminer, but the above percentage was 59.1-63.6% for the scale insects. Moreover, the percentage of farmers who believed in the economic profit of control, and thus believed in applying a collective national control program was 90.9-95.4% for the scale insects and 95.4% for the leafminer. The rate of infestation with both types of insect pests obtained on the different varieties of citrus trees in Tulkarm area was 30.5-54.5%. The most commonly used insecticides by the farmers to control both types of insect pests were Neoron and Superacid. Superacid was also mixed with the Folic oil to control the leafminer or with Neoron to control scale insects. Farmers also apply Folic oil alone to control scale insects. Other insecticides such as Vertimec and Confidor were used by the farmers to control the leafminer. Overall results indicate the presence of high percentage of farmers included in the questionnaire (60-70%) who made benefit from agricultural extension services and applied the recommended types and doses of insecticides to control both types of insect pests, but the percentage of infestation with these insects remained high (30-50%). This could be probably attributed to the inefficacy of recommended types or doses of insecticides or to the inappropriate application time of insecticides, therefore additional studies are needed to test the efficacy of applied insecticides or to search for more effective insecticides under laboratory and field conditions. Other non-chemical control measures (e.g., biological means) that were included in the questionnaire were not applied by the farmers.